(untitled) - Encyclopaedia Britannica Educational Corporation (Chicago, Ill. : Encyclopaedia Britannica Educational Corp., 1995)
A multimedia system designed for teaching and learning geography. Features include: geographic inquiry into global issues (GIGI) student lessons in English and Spanish; index and key topic searches of the GIGI text; instant access to Geopedia with its hundreds of charts, maps, data and learning activities; resource management software; videodisc clips and student research and report capabilities.
Electronic reproduction.
System requirements: IBM-compatible PC with 286/16MHz processor (386 processor recommended); 1MB RAM; DOS 5.0 or higher; VGA graphics board; 6.5MB hard drive (8.5MB using Tandy with DAC audio); 532K conventional memory free; CD-ROM drive (150Kps); Microsoft-compatible mouse; Sound Blaster or compatible sound device, and speakers or headphones recommended.
Title from container.
Ed. statement from disc label.
grades 7-12.
s
Keywords: Geography -- Databases; Atlases -- Databases